2013
DOI: 10.1111/ibi.12054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental calcium availability, egg parameters and laying order on Great TitParus majoreggshell pigmentation patterns

Abstract: Many bird species lay eggs speckled with protoporphyrin-based spots, however, for most of them the function of eggshell spotting is unknown. A plausible hypothesis is that protoporphyrin might have a structural function in strengthening the eggshell and is therefore deposited when calcium is scarce. In this study, we experimentally provided Great Tit Parus major females with supplemental calcium to examine its effect on the protoporphyrin-based maculation of their eggs. In addition, we studied variation in egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…In additon, the Great Tit has no brood parasites, and birds do not eject distinct-looking eggs (Kempenaers et al 1995, R. Hargitai personal observation). In a previous study, we showed that the distribution of eggshell spots was related to eggshell thickness in our Great Tit population (Hargitai et al 2013), suggesting a structural function of shell pigmentation (Solomon 1997, Gosler et al 2005, but the intensity and size of spots were not related to eggshell thickness (Hargitai et al 2013). In this study, we first tested whether eggshell spotting pattern was related to female characteristics that may indicate condition and state of health (body condition, body size, plasma oxidative status, plasma leukocyte count, and clutch size).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In additon, the Great Tit has no brood parasites, and birds do not eject distinct-looking eggs (Kempenaers et al 1995, R. Hargitai personal observation). In a previous study, we showed that the distribution of eggshell spots was related to eggshell thickness in our Great Tit population (Hargitai et al 2013), suggesting a structural function of shell pigmentation (Solomon 1997, Gosler et al 2005, but the intensity and size of spots were not related to eggshell thickness (Hargitai et al 2013). In this study, we first tested whether eggshell spotting pattern was related to female characteristics that may indicate condition and state of health (body condition, body size, plasma oxidative status, plasma leukocyte count, and clutch size).…”
Section: Introductionmentioning
confidence: 71%
“…Several hypotheses have been proposed to explain the pigmentation of bird eggshells (Kilner 2006, Reynolds et al 2009, Maurer et al 2011a); these hypotheses may not be mutually exclusive and could share similar predictions. Protoporphyrin-based eggshell pigmentation may promote camouflage (Stoddard et al 2011, Lovell et al 2013; it may enhance egg mimicry or permit egg recognition in species exposed to brood parasites (Stokke et al 1999, Soler et al 2000, Moskát et al 2008; it may help resist bacterial penetration into the egg (Ishikawa et al 2010, Fargallo et al 2014; or it may structurally strengthen eggshells (Gosler et al 2005, García-Navas et al 2010, Bulla et al 2012, Hargitai et al 2013, the latter of which is possibly the most plausible explanation for shell spotting patterns in cavity-nesting birds (Solomon 1997, Cherry andGosler 2010). Furthermore, Moreno and Osorno (2003) proposed that eggshell color could be a sexually selected signal, which may advertise the quality of the female and that of her offspring to the male parent in order that he contribute more to the breeding attempt (sexually selected eggshell coloration [SSEC] hypothesis).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is possible that eggshell pigments modify the amount and wavelength of light transmitted through the eggshell and thus affect embryonic development (Maurer et al 2015, Lahti andArdia 2016), or they may play a thermoregulatory role (Bakken et al 1978, Westmoreland et al 2007). Pigments may also decrease trans-shell contamination by microbes (Ishikawa et al 2010, but see Fargallo et al 2014), or they may strengthen thin eggshells (Gosler et al 2005, García-Navas et al 2010, Hargitai et al 2013. Finally, according to the sexually selected eggshell coloration hypothesis Osorno 2003, Soler et al 2008), eggshell colour may signal the quality of the female to the male parent, and colour intensity could be used by males as a cue to determine their effort in parental care.…”
Section: Introductionmentioning
confidence: 99%
“…Protoporphyrinbased eggshell pigmentation may help to provide camouflage (Stoddard et al 2011), it may enhance egg mimicry or allow individual egg recognition in species exposed to brood parasites (Stokke et al 1999;Moskát et al 2008), it may reinforce eggshells (Gosler et al 2005;García-Navas et al 2010;Hargitai et al 2013), or it may signal the quality of the female and the egg to the male in order to stimulate more intense paternal care (Moreno and Osorno 2003;Sanz and García-Navas 2009;Stoddard et al 2012;Hargitai et al 2016b). The accumulation of protoporphyrin has been reported to induce oxidative stress, leading to an increase in the activity of antioxidant enzymes to avoid oxidative damage (Afonso et al 1999;Pimentel et al 2013).…”
Section: Introductionmentioning
confidence: 99%